Loess and soils in the eastern Ebro Basin. (30th July 2015) - Boixadera, Jaume; Poch, Rosa M.; Lowick, Sally E.; Balasch, J. Carles
Abstract: Wind-blown sandy and silty deposits were formed during the late Quaternary in the NE Iberian Peninsula. They are the most significant in the West Mediterranean region, together with those described in the Tagus River basin (Iberian South Subplateau), forming small scattered patches across parts of the SE Ebro Depression and SW Catalan Mediterranean Range. Two major depositional environments are distinguished. The first (largest) outcrop covers the lower Ebro reaches on the SE border of the Ebro Depression, the Prelitoral Coastal Range and the Móra d'Ebre Basin. A second outcrop, to the north, consists of a few patches scattered over a wide amphitheatre surrounding the western tributaries of the Segre River, from the wind-exposed Segrià platforms to the Almenara Range in its northernmost part. They consist of highly sorted fine sands and silts, 1–12 m thick (though most typically 3–4 m thick), and coarser than typical loess. They are highly uniform, lack any sedimentary structures and are pale ochre. The deposits are calcareous (30–45% CaCO3 ), basic to alkaline and with some soluble salts. Five selected sequences of primary loess (namely Mas de l'Alerany, Tivissa, Guiamets, Batea and Almenara) were studied to ascertain deposit characteristics and soil development. All sections show a consistent vertical granulometric variability that may be attributed to wind intensity changes, and hinders the recognition of spatial particle size distribution. Pedogenesis is mostly related to calcium carbonate redistribution, which accumulates as nodules, large rhizocretions or biogenic calcite. Secondary gypsum (Batea and Almenara sequences) is probably related to primary gypsum blown from the source areas that was redistributed by leaching and precipitation at the bottom of the profiles. In a few places (Mas de l'Alerany outcrop) a fersialitic, rubefacted-recalcified soil indicates the presence of an older generation of loess. While the dominant WNW winds and particle coarseness suggest that the loess originates from nearby alluvial fans and fluvial plains, the presence of gypsum and Mg anomalies may be evidence of more distant sources of the Central Ebro Depression and Ondara-Corb alluvial fans. Optical Stimulated Luminiscence (OSL) ages for the more recent deposits (Guiamets, Batea, Almenara) are between 18 and 34 ka, while the old Mas de l'Alerany sequence is more than 115 ka. These ages indicate loess deposition during the last cold phases of the Quaternary and with pedogenesis occuring during warm interglacial periods.